Vancomycin-Dependent Enterococcus faecalis Clinical Isolates and Revertant Mutants - Van Bambeke, Françoise (American Society for Microbiology, 1999)
Three vancomycin-dependent clinical isolates of Enterococcus faecalis of the VanB type were studied by determining (i) the sequence of the ddl gene encoding the host d-Ala:d-Ala ligase and the vanS(B)-vanR(B) genes specifying the two-component regulatory system that activates transcription of the vanB operon, (ii) the level of expression of resistance genes by using dd-dipeptidase activity as a reporter, and (iii) the proportions of the peptidoglycan precursors synthesized. Each strain had a mutation in ddl leading to an amino acid substitution (D295 to V; T316 to I) or deletion (DAK251-253 to E) at invariant positions in d-Ala:d-Ala, d-Ala:d-Lac, and d-Ala:d-Ser ligases. These mutations resulted in impaired host d-Ala:d-Ala ligases since only precursors terminating in d-Ala-d-Lac were synthesized under vancomycin-inducing conditions. Two types of vancomycin-independent revertants of one isolate were obtained in vitro after growth in the absence of vancomycin: (i) vancomycin-resistant, teicoplanin-susceptible mutants had a 6-bp insertion in the host ddl gene, causing the E251-to-EYK change that restored d-Ala:d-Ala ligase activity, (ii) constitutive vancomycin-resistant, teicoplanin-resistant mutants had substitutions (S232 to F or E247 to K) in the vicinity of the autophosphorylation site of the VanS(B) sensor and produced exclusively precursors ending in d-Ala-d-Lac. Vancomycin- and teicoplanin-dependent mutants obtained by growth in the presence of teicoplanin had an 18-bp deletion in VanS(B), affecting residues 402 to 407 and overlapping the G2 ATP binding domain. The rapid emergence of vancomycin-independent revertants in vitro suggests that interruption of vancomycin therapy may not be sufficient to cure patients infected with vancomycin-dependent enterococci.